2011
DOI: 10.4314/gmj.v45i1.68921
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of ameloblastoma of the jaws in children

Abstract: In terms of long term cure for this tumour, enucleation has limited benefits. In children however, especially in those afflicted with the unilocular type, enucleation may be used as an interim procedure for the mandible to achieve further growth before carrying out a more appropriate definitive surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 9 publications
1
10
2
Order By: Relevance
“…Arotiba et al 6 , Huang et al 23 and Wenlu et al 28 all reported higher ratio of multicystic types than the unicystic types. On the contrary, Ord et al 2 , Abdulai 29 reported higher number of the unicystic type in their various studies, hence, our finding appeared to differ with the notion that most ameloblastoma in children arises from odontogenic cysts. 2,15 The solid type seen more in the older paediatric age group conformed with the other studies that suggested that this type of tumour is the commonest form found in the African child and resembles the adult variety 2 ,even though it could also be due to the late presentation of these patients.…”
Section: Discussioncontrasting
confidence: 82%
See 3 more Smart Citations
“…Arotiba et al 6 , Huang et al 23 and Wenlu et al 28 all reported higher ratio of multicystic types than the unicystic types. On the contrary, Ord et al 2 , Abdulai 29 reported higher number of the unicystic type in their various studies, hence, our finding appeared to differ with the notion that most ameloblastoma in children arises from odontogenic cysts. 2,15 The solid type seen more in the older paediatric age group conformed with the other studies that suggested that this type of tumour is the commonest form found in the African child and resembles the adult variety 2 ,even though it could also be due to the late presentation of these patients.…”
Section: Discussioncontrasting
confidence: 82%
“…This finding is comparable to most African studies where the researchers reported multilocular radiolucency as the commonest radiographic presentation. 6,19,20,21 On the contrary, Huang et al 23 , Khan et al 26 , and Wenlu et al 29 reported unilocular type to be more common. The mandible is the commonest site of presentation of the tumour in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[26] In children due to the rapid regeneration potential and increased rate of growth enucleation can be done as an interim procedure to avoid morbidity. [27] The conventional treatment for various forms of ameloblastoma has shown different prognosis depending upon the site, size, age and aggressiveness of the tumor. No defi nitive treatment procedures for individual variants are mentioned in the literature.…”
Section: Treatmentmentioning
confidence: 99%